Town and Country Reptiles: A Review of Reptilian Responses to Urbanization - French, Susannah S.; Webb, Alison C.; Hudson, Spencer B.; Virgin, Emily E. (Integrative and comparative biology, 2018)
The majority of the world population is now inhabiting urban areas, and with staggering population growth, urbanization is also increasing. While the work studying the effects of changing landscapes and specific urban pressures on wildlife is beginning to amass, the majority of this work focuses on avian or mammalian species. However, the effects of urbanization likely vary substantially across taxonomic groups due to differences in habitat requirements and life history. The current article aims first to broaden the review of urban effects across reptilian species; second, to summarize the responses of reptilian fauna to specific urban features; and third, to assess the directionality of individual and population level responses to urbanization in reptile species. Based on our findings, urban research in reptilian taxa is lacking in the following areas: (1) investigating interactive or additive urban factors, (2) measuring multiple morphological, behavioral, and physiological endpoints within an animal, (3) linking individual to population-level responses, and (4) testing genetic/genomic differences across an urban environment as evidence for selective pressures.